Supervisi Akademik Kepala Madrasah dalam Meningkatkan Kinerja pada Kegiatan Belajar Mengajar Guru - M. Adnan (Literasi: Jurnal Pendidikan Guru Indonesia, 2023)
The aim of this research is to describe the academic supervision of madrasah principals in improving the performance of teaching and learning activities at MTsN 1 Bima City, including teaching plans, learning processes, learning evaluations, and academic supervision techniques of madrasah principals. This research uses a qualitative descriptive method and data collection techniques are interviews and observation. The objects of this research are madrasa heads and teachers. The results show that teachers have implemented the madrasa head's supervision points in improving the teaching performance of teachers at MTsN 1 Bima City according to the character of the madrasa.